Characterisation of Refractory Wastes at Heavy Oil-Contaminated Sites: A Review of Conventional and Novel Analytical Methods - Whittaker, Martin; Pollard, Simon J. T.; Fallick, Tony E. (Environmental technology, 1995)
Methods for the analysis of petroleum hydrocarbons in contaminated soil and water are subject to a range of constraints arising from the complexity of waste-soil-groundwater matrices, the inherent chemical diversity of the spilled product and the requirements of the site investigation. The analytical uncertainties associated with refractory weathered contaminants, which exist as pockets of residual saturation in the contaminated subsurface are a major problem. Adoption of a transparent, phased approach to waste characterisation significantly mitigates these constraints and improves the use of site investigation resources. Moreover, the use of biomarker monitoring and gas chromatography-stable carbon isotope ratio mass spectrometry within such a scheme is likely to be of significant benefit to remediation experts in the elucidation of waste source terms and the selection and monitoring of remedial treatment technologies.